The use of manga for teaching reading: An investigation into the insertion of Japanese literature with primary school students (Research, Society and Development, 2023)
Manga can be seen as a teaching tool, allowing the student to be the protagonist of the process of encounter between the word and the subject who reads and establishing an experience that can modify the conception that both have of the world and of their own existences. The main objective of this article is to investigate the acceptance of the use of Mangas as a methodological practice in the classroom, as well as to analyze the contribution that they have been bringing to students after a school term participating in activities with readings with this new literature. In order to verify the students' acceptance of this methodology, we carried out an investigation study of the initial conceptions through an investigative questionnaire. With the result of the investigation, it was possible to find elements that allow the use of manga as part of the teaching and learning process and also to perceive the potential of such materials as didactic resources capable of contributing to the mediation and teaching of content and concepts of Portuguese Language and New Literatures.